Development and evaluation of a “simulator-based” ultrasound training program for university teaching in obstetrics and gynecology–the prospective GynSim study - Weimer, Johannes; Recker, Florian; Hasenburg, Annette; Buggenhagen, Holger; Karbach, Karla; Beer, Lia; Weimer, Andreas; Schiestl, Lina; Lorenz, Liv; Kloeckner, Roman; Dionysopoulou, Anna (Frontiers in Medicine, 2024)
Introduction This study addresses the challenges of ultrasound education in obstetrics and gynecology, focusing on the potential benefits of simulation techniques in medical training. Aiming to evaluate the impact of a structured simulator-based training program, this prospective, randomized, interventional study examines its effects on educational outcomes for 5th year medical students. Methods A total of 153 medical students were randomized into two groups: one receiving both theoretical instruction and hands-on ultrasound simulator training (study group), and the other receiving only theoretical instruction (control group). The study assessed theoretical knowledge and practical skills at two time points: upon enrollment and at the end of the course. The practical skills were specifically evaluated using a dedicated test on the ultrasound simulator. Results Out of 153 students, 113 completed the study (study group n=59, control group n=54). The students in the study group demonstrated a greater improvement in theoretical test scores. They also achieved better results at the practical test, with regard to image quality, accuracy, and efficiency. Both groups showed an increase in self-confidence and competency in performing ultrasound examinations independently. Students expressed high satisfaction with the course and a positive attitude toward simulator-based training. Discussion Simulator-based training presents a valuable supplement to traditional clinical education methods in obstetrics and gynecology. This approach is particularly effective in overcoming the challenges posed by the sensitive nature of gynecological examinations in medical student training. The study highlights the benefits of integrating simulator-based methods into medical curricula, improving both theoretical and practical ultrasound skills among students.